The Rigths of Indigenous People to their Own Law - Cianciardo, Juan Carlos Mariano (2012)
The aim of this paper is to analyze an interesting case about the rights of the indigenous peoples to their own law. In this case, an Argentinean court had to solve a conflict originated in the hypothetical right of a member of the wichí community to have sexual intercourse with his concubine’s daughter, based on an alleged indigenous custom. The paper tries to prove that the claim of the accused is unacceptable, because it affects the universality of some of the human rights present in the case.